CREATION OF A PSYCHOLOGICALLY SAFE EDUCATIONAL ENVIRONMENT FOR STUDENTS - Курманаева, А.М.; Возных, Е.И.; Сакауова, Ю.А. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The relevance of the study lies in the fact that in connection with the ongoing social changes and modernization of Russian education, the problem of creating a safe learning environment for children, as well as ensuring psychological safety in the interaction of participants in the relationship formed in the educational environment, is becoming quite relevant. The aim of the study was the selection, substantiation, and disclosure of the psychological factors of the educational environment that influence the psychological well-being of pupils. Thus, the solution of the problems of psychological safety in the educational environment, in particular the psychological distress of children and adolescents, should be carried out through programs and methods for diagnosing the personality and building individual corrective and preventive work in accordance with personal characteristics.
Keywords: safety; education; environment